Penerapan Metode Dempster Shafer Untuk Diagnosa Penyakit Batu Karang - Vina Winda Sari; Muhammad Zunaidi; Asyahri Hadi Nasyuha; Marsono Marsono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Rocks or urinary tract stones are small and hard deposits that form in the kidneys, urinary tract and often cause pain when urinating, due to lack of public knowledge about the problem of coral disease, and to find out about this situation, people usually do an examination at the home. Sick or Doctor. However, not everyone can do this, this can be due to insufficient economic factors or long distances to visit the doctor, there are also weaknesses in the limited working hours of the doctor's practice. Therefore, innovations and solutions are needed in these conditions, namely by utilizing computer technology to build an expert system that has the ability as a doctor in making diagnoses. This study aims to create an expert system analysis with the Dempster Shafer method that can help doctors and physician assistants, or the general public in diagnosing coral stone disease. The results of this study indicate that with the analysis of the Dempster Shafer method, more optimal and accurate diagnostic results related to coral disease are available to the general public and can assist in the examination of coral disease.